The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1002/glia.20677
|View full text |Cite
|
Sign up to set email alerts
|

Differential neutrophil infiltration contributes to regional differences in brain inflammation in the substantia nigra pars compacta and cortex

Abstract: Brain inflammation is a suggested risk factor for neurodegenerative disease. Interestingly, severe inflammation in the substantia nigra pars compacta (SNpc) accelerates the onset and progression of Parkinson's disease. In this study, we examined the underlying mechanisms of severe inflammation in the SNpc by comparing the inflammatory process with that in the cortex. In intact brain, the densities of CD11b 1 microglia were similar in the SNpc and cortex. However, lipopolysaccharide injection enhanced the CD11b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 36 publications
3
70
1
1
Order By: Relevance
“…Neutrophils are a major source of proinflammatory mediators including iNOS, Cyclooxygenase-2, Monocyte chemotactic protein-1, which play important roles in neuronal death within LPS-injected and/or ischemic brains (Ji et al, 2007;Matsumoto et al, 2007). Previously, we found that direct injection of LPS recruited more neutrophils to the SN than to the cortex or hippocampus, which suggests that susceptibility to LPS neurotoxicity may differ among these regions (Figure 2B LPS SN; Ji et al, 2008). LPS iv injection recruited fewer neutrophils than did direct LPS injection ( Figure 2B), and induced only transient expression of inflammatory mediators, lasting for up to 1-3 d (Figure 1-3).…”
Section: Discussionmentioning
confidence: 86%
“…Neutrophils are a major source of proinflammatory mediators including iNOS, Cyclooxygenase-2, Monocyte chemotactic protein-1, which play important roles in neuronal death within LPS-injected and/or ischemic brains (Ji et al, 2007;Matsumoto et al, 2007). Previously, we found that direct injection of LPS recruited more neutrophils to the SN than to the cortex or hippocampus, which suggests that susceptibility to LPS neurotoxicity may differ among these regions (Figure 2B LPS SN; Ji et al, 2008). LPS iv injection recruited fewer neutrophils than did direct LPS injection ( Figure 2B), and induced only transient expression of inflammatory mediators, lasting for up to 1-3 d (Figure 1-3).…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, BBB leakage has been observed in PD patients [344] as well as in animal models of PD [345,346]. Interestingly, the substantia nigra region is reportedly more prone to BBB disruption and neutrophil infiltration than is the cortical region [347].…”
Section: B) Parkinson's Diseasementioning
confidence: 99%
“…Chemokines are implicated in the pathogenesis of a number of neurologic diseases, including Alzheimer's disease, cerebral ischemia, and multiple sclerosis (4). Chemokines are major effector molecules recruiting blood inflammatory cells to the injury site (5), and recently, several studies have reported that blood inflammatory cells also enter the injured brain and participate in brain inflammation (6)(7)(8). In particular, CCL2 (MCP-1) and CCL3 (MIP-1a) are important chemokines associated with monocyte infiltration into the injured brain (9)(10)(11)(12).…”
mentioning
confidence: 99%